Portrait of David Flatman - Ede, Gary, 1946- (2001)
"David Flatman is film producer, David Flatman productions."--Notes from artist.
Condition: Good.
Title supplied by artist, see acquisition file number 204/08/00063-02.
Part of the collection of photographs of portraits of prominent Australians.
Also available online
Keywords: Flatman, David -- Portraits; Motion picture producers and directors -- New South Wales -- Sydney -- Portraits; Film producers and directors